Literatur Review: Pengaruh Aplikasi Wordwall terhadap Minat Belajar pada Anak Usia Dini: Literature Review: The Effect of the Wordwall Application on Interest in Learning in Early Childhood - Nabila Zakiyyatul Af’idah (Universitas Ngudi Waluyo, 2024)
A strong interest in learning during the early stages is considered crucial in forming a solid foundation for learning and developing intrinsic motivation towards the learning process. The aim of this research is to investigate the impact of using the Wordwall application on the learning interest of young children. This study is a literature review aimed at exploring how the Wordwall application affects the learning interest of young children. The methodological approach employed in this research is literature analysis. The data sources analyzed include scientific articles and other relevant literature discussing the impact of the Wordwall application on the learning interest of young children. Findings from various literature indicate that the Wordwall application has significant potential in enhancing the learning interest of young children. Through an interactive and enjoyable approach, this application effectively stimulates children's interest in learning. This research is expected to provide valuable and relevant insights for educators, researchers, and Wordwall application developers, as well as make a positive contribution to the development of early childhood education. ABSTRAK Minat yang kuat dalam pembelajaran pada tahap awal dianggap sangat penting dalam membentuk dasar pembelajaran yang kokoh dan mengembangkan motivasi intrinsik terhadap proses belajar. Tujuan dari penelitian ini adalah untuk menyelidiki dampak penggunaan aplikasi Wordwall terhadap minat belajar pada anak usia dini. Penelitian ini merupakan sebuah tinjauan literatur yang bertujuan untuk menemukan bagaimana aplikasi Wordwall memengaruhi minat belajar pada anak usia dini. Pendekatan metodologi yang digunakan dalam penelitian ini adalah analisis literatur. Sumber data yang dianalisis termasuk artikel ilmiah dan literatur lain yang relevan yang membahas dampak aplikasi Wordwall terhadap minat belajar anak usia dini. Temuan dari berbagai literatur menunjukkan bahwa aplikasi Wordwall memiliki potensi besar dalam meningkatkan minat belajar anak usia dini. Dengan pendekatan interaktif dan menyenangkan, aplikasi ini efektif dalam membangkitkan minat belajar anak-anak. Penelitian ini diharapkan memberikan wawasan yang berharga dan relevan bagi pendidik, peneliti, dan pengembang aplikasi Wordwall, serta memberikan kontribusi positif terhadap perkembangan pendidikan anak usia dini.